2021
DOI: 10.3389/fonc.2021.705335
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification for Organ/Space Surgical Site Infection in Advanced Digestive System Cancer

Abstract: BackgroundOrgan/space surgical site infection (organ/space SSI) is a serious postoperative complication, closely related to a poor prognosis. Few studies have attempted to stratify the risk of organ/space SSI for patients with advanced digestive system cancer. This study aimed to identify a simple risk stratification for these patients based on perioperative factors.MethodsThe study was based on two randomized controlled trials (RCT) (NCT02715076, ChiCTR-IPR-17011099), including 839 patients undergoing electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Many of the previously studied surgical populations have much lower rates of overall and organ/space SSI than PT recipients. 21 Patients with organ/space SSIs often receive prolonged courses of antibiotics, which would likely lead to more CDI than perioperative prophylaxis alone. Additionally, most of the agents used for perioperative prophylaxis in the PT population are targeted at enteric organisms rather than skin flora, which have higher risk for CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the previously studied surgical populations have much lower rates of overall and organ/space SSI than PT recipients. 21 Patients with organ/space SSIs often receive prolonged courses of antibiotics, which would likely lead to more CDI than perioperative prophylaxis alone. Additionally, most of the agents used for perioperative prophylaxis in the PT population are targeted at enteric organisms rather than skin flora, which have higher risk for CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent surgeries are often a contaminated or infected condition in clinical practice, however, it is controversial whether an emergent surgery is a risk factor of SSI incidence or not. [24][25][26] We placed subcutaneous drain or performed closed incision negative pressure therapy when the operative wound was highly contaminated. These treatments might reduce the SSI incidence in patients with operative wound class III/IV.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous reports revealed that neoadjuvant chemotherapy, radiotherapy, preoperative parenteral nutrition, prolonged intensive care unit stay, disseminated cancer, preoperative sepsis, prevalence of inflammatory bowel syndrome, and bowel obstruction/perforation/ fistula were identified as risk factors of organ/space SSI. 25,26 Furthermore, Gomila et al and Xu et al also clarified that stoma creation in colorectal surgery was the risk factor of organ/space SSI. Although our cohort included the largest number of patients undergoing lower gastrointestinal surgery, previously mentioned risk factors were not considered as adjustment factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSIs affect up to 10–20% of patients undergoing major surgery [ 1 ]. In the USA, SSIs cause over 90,000 readmissions, extend the average length of hospital stay by up to 9.7 days and increase medical costs by $700 millions each year [ 2 ]. Due to their aggressive character, cardiac surgical procedures are associated with an even greater degree of postoperative infection risk.…”
Section: Introductionmentioning
confidence: 99%